Structural Equation Model Approach to National Health Insurance Participation in Disadvantaged Regions - Nurul Rezki; Siswanto Siswanto; Musdalifah Musdalifah; Evaletrina Gracelita Marisda; Ismail Dwi Saputra (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2025)
Kartu Indonesia Sehat is Indonesia's national health insurance program, which is a right for everyone. However, the distribution of the program is not evenly distributed, especially in disadvantaged, frontier, and outermost regions. This research examines the factors influencing participation rates in Indonesia's national health insurance, the Healthy Indonesia Card program, in disadvantaged, frontier, and outermost regions of South Sulawesi. There are seven variables to estimate these factors, including education, employment, income, knowledge, motivation, socialization and trust. Based on descriptive statistics and a Structural Equation Model Partial Least Squares analysis using bootstrap parameters, there are three influencing factors: occupation, motivation, and trust, with a goodness of fit model of 32.3568%.